Development of OnlineWeb-Based New Student Graduation Application in Junior High School - Jusmita Weriza; Ismail Husein; Noranizamardia Noranizamardia; M Fakhariza; Khairan Marzuki (Universitas Bumigora, 2022)
The student graduation information system is integral to managing and carrying out school information system activities. Especially in Junior High Schools (SMP) today, many still have not used a website-based information system due to the new internet network entering this area. In meeting the admin’s need, in particular, to deal with the problem of passing the distribution of receiving information or announcements, documentation of activities, teaching materials, and registration of new student participants have not run optimally as expected. In the system development method in this research, the author uses the System Development Life Cycle (SDLC) with the Waterfall model approach, which consists of 5 stages: analysis, design, implementation, testing, and implementation. The system design tool uses the UML (Unified Modeling Language) method using use-case diagrams according to system requirements. In developing the SDLC method in this study, the authors used it until the design stage. The results obtained from this research are a Web-based application system for new students’ graduation. With this tool, several related files will be generated. This new system can improve the quality of further student admissions, graduation information and school information through the website.